Comparison of a high throughput day case atrial fibrillation ablation service in a local hospital with standard regional tertiary cardiac centre care. Issue 3 (30th July 2018) - Opel, Aaisha; Mansell, Josephine; Butler, Alison; Schwartz, Rhona; Fannon, Michael; Finlay, Malcolm; Hunter, Ross J; Schilling, Richard J
Abstract: Aims: We investigated safety and efficacy of a high throughput atrial fibrillation (AF) ablation service within a local non-cardiac centre compared with matched patients at the regional tertiary cardiac centre. Methods and results: Patients were consented in clinic and pre-assessed by clerical staff. Locally, other than physicians, staff had no experience of ablation and were trained with simulations. Pulmonary vein isolation (PVI) was performed with conscious sedation, on uninterrupted anticoagulation for at least 4 weeks. No transoesophageal echocardiogram (TOE) was performed. A 28 mm Arctic Front Advance Cryoballoon was used. A 20 mm Achieve wire demonstrated PVI on a portable laptop-based EP recording system. Phrenic nerve function was monitored during right PVI. Finally, a transthoracic echocardiogram excluded a pericardial effusion. A Femostop was applied. Two hundred and seventy-six patients were matched. Average age was 61 ± 0.7 years, 39% female. CHA2 DS2 VASc score varied from 0 to 7. Procedure time was significantly shorter at the local hospital (63.5 ± 1.1 vs. 101.7 ± 2.9 min, P  < 0.0001). Fluoroscopy time (5.5 ± 0.2 vs. 12.6 ± 0.6 min, P  < 0.0001) and fluoroscopy dose were lower (17.2 ± 2.1 vs. 97.6 ± 14.6 mGy, P  < 0.0001). Successful PVI was achieved in all. The complication rate was low (5.4% vs. 6.3%, P = not significant). Four (1.4%) patients were not day case discharges. At 3 month follow-up, 54.3% had complete resolution, and 26.1% had improvement of symptoms. A total of 16.6% patients requested repeat procedures for ongoing symptoms. Conclusion: In experienced hands, cryoballoon for paroxysmal AF is delivered safely and effectively in a local centre. Outcomes remain excellent. These short, day case procedures allow utilization of non-cardiac centres. The service provides a model to meet increasing demands.